“Estudio Técnico – Económico para la instalación de una planta procesador de mermelada a partir de tomate (licopersicon esculentum M. ), carambola (Averroha carambola L.), uva ( vitis labrusca) y cocona (solanumsessiliflorum D. ) en la provincia de San Martín - Navarro Ramírez, Enrique (1997)
In our region and almost in all the country currently not is offer products elaborated based fruit tropical, however the industrialization of these in juices, jams, nectars, etc. would have the option of move to them current products made of fruit traditional. In the region San Martín produces around 10000 metric tons/year of fruits such as carambola, grapes, eocena and tomato; which are consumed 25% directly and 75% for ·ser exploited and processed industrially. The demand for jams in the San Martin region is for 1997 193 TM; by what the project designed a processing plant with production capacity of 5000 Kg per month covering a 34, 38% of the demand insatis.fecha (1997), using 40% of the production capacity in the first year, then there will be 8750 Kg per month, 12500 Kg per month to the second and third year respectively. Machinery and equipment selected for the production process are offered almost in its...